Assessment of Levels and Motivators of Edupreneurship Intentions among Undergraduates of Emmanuel Alayande University of Education, Oyo State - AKANBI, Samuel Toyin (Ilorin Journal of Education, 2025)
This study intended to examine the level of edupreneurial intention and the motivating factors among undergraduate education students. A cross-sectional survey design was adopted. A sample of 352 students from Emmanuel Alayande University of Education who enrolled in education-related courses was selected through stratified random sampling. The Edupreneurship Intention Scale (α = .87) was used to collect data on participants’ entrepreneurial aspirations within the educational sector. Descriptive statistics (including frequency counts, means, and standard deviations) were employed to analyse the data. The findings revealed that participants demonstrated a high level of intention toward edupreneurial activities, as reflected across key components such as attitude, perceived social norms, perceived behavioural control, and overall edupreneurial intention. Furthermore, while students exhibited both intrinsic and extrinsic motivation, the results indicated that intrinsic motivation which is rooted in personal fulfilment, passion for educational impact, and self-confidence, served as the more powerful driving force. The study concluded that for edupreneurial intention to be successfully transformed into reality, institutions and policymakers must prioritise the development of supportive structures. These should include mentorship, funding opportunities, legal guidance, and social support systems that foster an enabling environment, one that not only complements students’ internal motivation but also empowers them to realise their edupreneurial aspirations through tangible and impactful ventures.